2017
DOI: 10.1007/s12094-017-1633-2
|View full text |Cite|
|
Sign up to set email alerts
|

BRG1 regulation by miR-155 in human leukemia and lymphoma cell lines

Abstract: Our study revealed a previously unknown miR-155 heterogeneity that could result in differences in the treatment with miRNAs in our attempt to inhibit BRG1. However, the expression levels of BRG1 and miR-155, before prednisolone treatment were not statistically significantly associated prednisolone sensitive leukemia cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…miR-155 directly inhibited the expression of BRG1 and upregulated the subsequent VEGFC, but not VEGFD expression in NKTCLs miR-155 negatively regulated BRG1 expression in human leukemia cell lines. 30 To assess whether miR-155 directly inhibited BRG1 transcription, we cloned the 3-UTR sequence of BRG1 that contained the potential miR-155 binding site (WT) or a mutated sequence (MUT) into a luciferase reporter construct. As shown in Figure 2(a), miR-155 potently inhibited the luciferase activity from the WT but not from the MUT construct, suggesting that miR-155 can directly and specifically inhibit the transcription of BRG1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-155 directly inhibited the expression of BRG1 and upregulated the subsequent VEGFC, but not VEGFD expression in NKTCLs miR-155 negatively regulated BRG1 expression in human leukemia cell lines. 30 To assess whether miR-155 directly inhibited BRG1 transcription, we cloned the 3-UTR sequence of BRG1 that contained the potential miR-155 binding site (WT) or a mutated sequence (MUT) into a luciferase reporter construct. As shown in Figure 2(a), miR-155 potently inhibited the luciferase activity from the WT but not from the MUT construct, suggesting that miR-155 can directly and specifically inhibit the transcription of BRG1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NKTCL cells, Cuadros et al reported the negative correlation between miR-155 and BRG1 in different lymphoma cells. 30 As either a tumor suppressor or an oncogene, BRG1 presented pleotropic phenotypes mostly through the association and expressional regulation of different target genes, such as: RB family proteins, [43][44][45] p21, 46 and p53, 47 for viability and cell cycle progression; p53, 47 BRCA1, 48 and FANCA 49 for DNA repair; CD44 50 and E-cadherin for cell adhesion; multiple genes in T-cell development and other immune functions 51 ; miR-550a-5p/RNF43/Wnt/β-catenin signaling 28 and miR-148b 52 for cancer metastasis. Recently, Zhu et al showed that by inhibiting the activation of STAT3 and subsequently the expression of VEGFC, BRG1 controlled lymphangiogenesis in colorectal carcinoma, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their previous study, it was found that a lack of BRG1 in lung tumors could be related to the action of different miRNAs, such as miR-155. The authors, in 2018, found that BRG1 levels were inversely proportional to miR-155 expression in Burkitt’s lymphoma and the diffuse large B cell lymphoma human cell line [ 27 ]. Chang et al, in 2019, reported that miR-155 regulates lymphangiogenesis in NKTCL through the miR-155/BRG1/STAT3/VEGFC pathways in human NKTCL cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…These findings managed to link inflammation to cell transformation during cancer [ 124 ]. miR-155 has been also identified to exhibit antiapoptotic effects, overexpressed in inflammatory conditions [ 125 ] and leukemia [ 126 ], and which is responsible for the repression of proapoptotic tumor p53-induced nuclear protein 1 [ 127 ]. On the other hand, overexpression of miR-146b alters the NF- κ B signaling pathway in an IL-6-dependent manner, leading to a decrease in the invasion rate of breast cancer cells [ 128 ].…”
Section: Molecular Inflammatory Events During Cancer Development Amentioning
confidence: 99%